TALÂKU'L-EKRAD VE TALÂKUS'S-SELÂS VE TALÂKU'S-SEKRÂN VE TUĞYÂNU'L-EVLIYÂ'I FI'L-ENKIHA LÎ MOLLÂ ABDULLAH EL-BEYTIVÂTÎ. DIRÂSE VE TAHKÎK - SITO, MOHAMDTAHR MOHAMDSALH (Fırat Üniveristesi, 2020)
Bu çalışma, Molla Abdullah el-Betvâtî'nin "Talâku'l-Ekrâd ve Talâku's-Selâs ve Talaku's-Sekrân ve Tuğyâni'l-Evliyâ'i fi'l-Enkiha" adlı eserinnin tahkik ve incelenmesini konu edinmiştir. Çalışmamız üç bölüm halinde hazırlanmıştır: Birinci bölümde müellifin hayatı ve ilmî kişiliği üzerinde durulmuştur. Bu bölümde müellifin adı, künyesi, doğumu, yetişmesi, hocaları, talebeleri, itikadi ve amelî mezhebi, eserleri ve vefatı hakkında bilgi verilmiştir. İkinci bölümde müellifi adı geçen eseri tanıtılmıştır. Bu bölümde eserin ismi, müellife nispeti, telif sebebi, konusu, kaynakları, yöntemi ve esere yöneltilen bazı eleştiriler gibi hususlar üzerinde durulmuştur. Üçüncü bölümde ise adı geçen eserin tahkiki yapılmıştır. Tahkike ayırılan bu bölümde ayet ve hadislerin tahricinin yanı sıra müellifin eserde yer verdiği fıkhi konuların da fıkıh mezheplerinin muteber kaynaklarından tahric edilmiştir. Ayrıca eserin gerekli yerlerine açıklama, hazf ve ekleme gibi bazı değerlendirmelerde bulunulmuştur Araştırdığımız kitapta, insanlar arasında bazı boşanma meselelerinin ele almaktadır. Yazar bu kitapta Kürtler tarafından kullanılan boşanma kelimelerini bahsetmektedir. Ayrıca boşanma ahkamları ve çeşitleri her birini tanımılmıştır. Yazar üç çekim, ihlal etme şertlerini ve dört mezhebe göre sarhoş halinde boşanma meselelerini göstermektedir. Sonra evliliğin esası ve sütunları, kötülüğün durumu hakkında yazıp baba kızını evlenmeye zorladı zamanda ve küçük yaşta evliliği onaylanmayıp ve bu konular hakkında onun asrında mevcut olan bazı geleneklere ve bazı fetvalara itiraz etmiştir. Anahtar kelimeler: Talâk, Rica, Nikâh, Delil, Fetva, Mezheb, Evliya

This study deals with the study and investigation of the book (Divorce of the three Kurds and divorce of the three, drunk divorce and tyranny of parents in marriage) for Mulla Abdullah Al-Baitwati (d. 1961) It has been divided into three chapters, chapter I a study on the life of the author and included the definition of the author's personal and scientific life, the definition of his name, nickname and lineage, and his birth, upbringing and death, and his studying the science, and his elders and disciples, and doctrinal and contract, and his books. Then, in the second chapter, the study dealt with the speech on the book, in terms of its name, description and attribution to the author, the reasons for its authoring, the subject of the book, the sources of the author therein, the author's curriculum in the book, some drawbacks to it, and the method of achieving it. And the third chapter has been devoted to the investigation of the book to further explain, attribution of the verses to its Surah, take out of the Hadiths and author from its sources, translation of its person's life, take out of the issues of jurisprudence or that are taken by the author from the trusted doctrinal books, documenting all the author's statements from the books of the scholars, and commenting on the places that need to be further explained or clarified. The book deals with some of the issues of divorce among people, and mentions the common words among the Kurds in their rhythm of divorce, as it shows the provisions of divorce and its divisions, and identifies each of them, and mentions the rule of the analysis and the collection fo the three divorce, and the drunken divorce of the four schools (Madh'hab), and responds to violators. Then the merits of marriage and its pillars, and the state of the evildoer, and the father forced his daughter to marry, and marrying a young girl, but he did not authorize them, and he objected to some current customs and some fatwas issued in his era. Keywords: Betwati, Divorce, Returning, Marriage, The guide, Religious opinion (Fatwa), Doctrine, Guardians (Awliya)
Kürtlerin boşanması, üç talakla boşanma, sarhoşun boşaması, nikâhlarda velilerin baskısı ve zulmü. Molla Abdullah el-Bitwatî. Tahkik çalışması (The divorce of the Kurds, the three divorce, the devorce of the drunk, the oppression of protector in marriage contract for Mollâ Abdullah el-Beytivâtî.Study and İnquiry
Keywords: Din